Fostering the adaptation of collaborative circular business models through digital platform-based ecosystems developing a matching algorithm: a design science research approach. - Rapp, Jannis (Stellenbosch : Stellenbosch University, 2023)
Thesis (MEng)--Stellenbosch University, 2023.